Prediction of Friction Torque in Paired Tapered Roller Bearings of Disc Cutter Under Tri-Axial Rock-Breaking Loads and Preload - Gang Hu; Chaoyu Yang; Huanqiang Li; Haiming Zhao; Zhihao Zhang (Lubricants)
The disc cutter is a key rock-breaking component of tunnel boring machines, and during operation, improper assembly preload often leads to uneven wear of the cutter. To study the effect of preload force on the friction torque of paired tapered roller bearings during rock-breaking, the transmission of preload and rock-breaking loads within the disc cutter structure is first analyzed, and a bearing load distribution model is established. Based on this model, a method for calculating the friction torque of the tapered roller bearings in the disc cutter, considering both external loads and preload force, is proposed. Next, finite element analysis is conducted to investigate the impact of preload displacement on preload force, and a relationship equation is derived using polynomial fitting. Finally, experiments on bearing preload displacement and friction torque are carried out under no-load conditions. The results show that the simulation results for the relationship between preload force and preload displacement are in good agreement with the experimental results. Additionally, the experimental results for the friction torque of the tapered roller bearings are close to the theoretical calculation results, with the overall trend matching, thus verifying the reliability of both the simulation and theoretical models.